Scales of Blue and Fin Whale Feeding Behavior off California, USA, With Implications for Prey Patchiness - Irvine, Ladd M.; Palacios, Daniel M.; Lagerquist, Barbara A.; Mate, Bruce R. (Frontiers in Ecology and Evolution, 2019)
Intermediate-duration archival tags were attached to eight blue whales (Balaenoptera musculus; four females, three males, one of unknown sex) and five fin whales (B. physalus; two females, one male, two of unknown sex) off southern California, USA, in summer 2014 and 2015. Tags logged 1-Hz data from tri-axial accelerometers, magnetometers, and a depth sensor, while acquiring Fastloc GPS locations. Tag attachment duration ranged from 18.3-28.9 d for blue whales and 4.9-16.0 d for fin whales, recording 1,030-4,603 dives and 95-3,338 GPS locations per whale across both species. Feeding lunges (identified from accelerometer data) were used to characterize “feeding bouts” (i.e., sequences of feeding dives with < 60 min of consecutive non-feeding dives), within-bout behavior, and to examine the spatial distribution of feeding effort. Whales fed near the tagging locations (Point Mugu and San Miguel Island) for up to 7 d before dispersing as far south as Ensenada, Mexico, and north to Cape Mendocino, California. Dispersal within southern California waters differed by sex in both species with males undertaking offshore, circuitous excursions, while females remained more coastal, suggesting that movement patterns on the feeding grounds may not be exclusively related to energy gain. Feeding bout characteristics were similar for both species, with the median bout having 24 dives and lasting 3.3 h for blue whales (n = 242), and 19 dives while lasting 2.7 h for fin whales (n = 59). Bout duration was positively correlated with the number of feeding lunges per dive within a bout for both species, suggesting whales left poor-quality prey patches quickly but fed intensively for up to 34.9 h when prey was abundant. Feeding bouts occurred further apart as the distance from shore increased, but there was no corresponding difference in the number of feeding lunges per dive, suggesting the whales were feeding at the same rate throughout their range, but that prey was more dispersed in offshore waters. This may be evidence of two feeding strategies, with spatially aggregated foraging around highly localized, topographically forced upwelling centers nearshore, and more dispersed foraging in larger areas of elevated, but patchy, productivity offshore.